2019
DOI: 10.1587/elex.16.20190528
|View full text |Cite
|
Sign up to set email alerts
|

A PVT variation-tolerant static single-phase clocked dual-edge triggered flip-flop for aggressive voltage scaling

Abstract: A novel static single-phase clocked (SSPC) dual-edge triggered flip-flop (DET-FF) is proposed to allow energy-efficient operation with aggressive voltage scaling. By employing two static latches with a singlephase clock, contention and clock phase mismatch is avoided, which significantly improves tolerance to PVT variations. The post-layout simulation performed with 28 nm CMOS technology shows that the proposed SSPC DET-FF consumes less power and has significantly better powerperformance trade off (PDP) than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…(%) DETFF TP t cq PDP LM1 [13] 36.18 31.68 16.19 LM2 [13] 2267.70 24.34 94.16 TCRFF [16] 26.48 39.59 55.71 LM C [15] 10.03 32.26 38.00 LG C [19] 21.99 41.80 54.72 IP C [19] 19.22 37.01 49.25 FN C [19] 4.68 34.15 37.41 EP1 [21] 51.05 4.88 53.56 EP2 [22] 66.58 5.36 64.89 SSPC [25] 7 3, the flip-flop proposed in this paper is superior to all the comparative DETFFs in terms of the total circuit power consumption, saving an average of 251.17% of the total power consumption. Moreover, it improved the average PDP by 44.32% and the delay by 9.71%.…”
Section: Experimental Results and Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(%) DETFF TP t cq PDP LM1 [13] 36.18 31.68 16.19 LM2 [13] 2267.70 24.34 94.16 TCRFF [16] 26.48 39.59 55.71 LM C [15] 10.03 32.26 38.00 LG C [19] 21.99 41.80 54.72 IP C [19] 19.22 37.01 49.25 FN C [19] 4.68 34.15 37.41 EP1 [21] 51.05 4.88 53.56 EP2 [22] 66.58 5.36 64.89 SSPC [25] 7 3, the flip-flop proposed in this paper is superior to all the comparative DETFFs in terms of the total circuit power consumption, saving an average of 251.17% of the total power consumption. Moreover, it improved the average PDP by 44.32% and the delay by 9.71%.…”
Section: Experimental Results and Comparative Analysismentioning
confidence: 99%
“…(%) DETFF G2 G4 LM1 [13] 48.71 58.02 LM2 [13] 94.72 94.73 TCRFF [16] 45.86 58.41 LM C [15] 28.23 43.05 LG C [19] 38.45 48.95 IP C [19] 17.95 19.57 FN C [19] 16.46 26.65 EP1 [21] 49.23 50.65 EP2 [22] 65.87 66.42 SSPC [25] 30.71 46.38 Average 43.62 51.28…”
Section: Variance Analysismentioning
confidence: 99%
“…Flip-flops occupy a large portion of chip area and contribute a significant part of overall power in the system. It has been reported that flip-flops and last sections of clock distribution network that directly drive flip-flops account for 90% of the clock system power [14,15,16]. It is crucial to design low-power radiation-hardened flip-flops with low penalties to meet strict demands of the industry.…”
Section: Introductionmentioning
confidence: 99%